Global Brain Perfusion and the Risk of Transient Ischemic Attack and Ischemic Stroke: The Rotterdam Study. Issue 7 (2nd April 2019) - Fani, Lana; Bos, Daniel; Mutlu, Unal; Portegies, Marileen L.P.; Zonneveld, Hazel I.; Koudstaal, Peter J.; Vernooij, Meike W.; Ikram, M. Arfan; Ikram, M. Kamran
Abstract : Background: The role of subtle disturbances of brain perfusion in the risk of transient ischemic attack (TIA) or ischemic stroke remains unknown. We examined the association between global brain perfusion and risk of TIA and ischemic stroke in the general population. Methods and Results: Between 2005 and 2015, 5289 stroke‐free participants (mean age, 64.3 years; 55.6% women) from the Rotterdam Study underwent phase‐contrast brain magnetic resonance imaging at baseline to assess global brain perfusion. These participants were followed for incident TIA or ischemic stroke until January 1, 2016. We investigated associations between global brain perfusion (mL of blood flow/100 mL of brain/min) and risk of TIA and ischemic stroke using Cox regression models with adjustment for age, sex, and cardiovascular risk factors. Additionally, we investigated whether associations were modified by retinal vessel calibers, small and large vessel disease, blood pressure, and heart rate. During a median follow‐up of 7.2 years (36 103 person‐years), 137 participants suffered a TIA and another 108 an ischemic stroke. We found that lower global brain perfusion was associated with a higher risk of TIA, but not with the risk of ischemic stroke (adjusted hazard ratio, 95% CI, per standard deviation decrease of global brain perfusion: 1.29, 1.07–1.55 for TIA and adjusted hazard ratio of 1.06, 0.87–1.30 for ischemic stroke). Across strata of wider arteriolar retinal calibers, lower brain perfusion was more prominently associated with TIA, but not with ischemic stroke. Conclusions: In a community‐dwelling population, impaired global brain perfusion increased the risk of TIA, but not of ischemic stroke.